2005
DOI: 10.1016/j.pain.2005.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression associated with migraine: Influence on migraine subjects' disability and quality of life, and acute migraine management

Abstract: Anxiety and depression are reported to be frequently associated with migraine but how they impact on migraine-related disability, migraine subjects' quality of life, and medical and therapeutic management of migraine attacks has not been investigated. FRAMIG 3 is a nation-wide population-based postal survey carried out in France according to the 2004 international classification of headache disorders. Subjects who had had migraine attacks during the last 3 months (subjects with 'active migraine', N = 1957) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
263
4
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(307 citation statements)
references
References 28 publications
29
263
4
11
Order By: Relevance
“…However, little is known about the impact of anxiety and depression on migraine-related disability and quality of life. Lantéri-Minet et al [12] found increased migraine disability and greater impairment in HRQOL when migraine was associated with anxiety and depression. The complex interaction of such characteristic psychiatric disorders with migraine subjects' well-being and functional status is poorly understood and under-recognised.…”
mentioning
confidence: 98%
“…However, little is known about the impact of anxiety and depression on migraine-related disability and quality of life. Lantéri-Minet et al [12] found increased migraine disability and greater impairment in HRQOL when migraine was associated with anxiety and depression. The complex interaction of such characteristic psychiatric disorders with migraine subjects' well-being and functional status is poorly understood and under-recognised.…”
mentioning
confidence: 98%
“…The impact of anxiety and depression on migraine was highlighted by a recent landmark study of the French population by Lantéri-Minet et al 12 Using a low threshold on the Hospital Anxiety and Depression Scale (HADS), they found that 51% of subjects with active migraine were anxious or depressed, but importantly 28% had anxiety alone. Depression alone was not found to be more frequent among migraine than non-migraine subjects in this survey, and screening for depression alone would have missed over half of those with significant psychiatric comorbidity.…”
Section: Discussion and Screening Recommendationsmentioning
confidence: 99%
“…11 Migraineurs with anxiety and depression also report lower satisfaction with headache treatment, increased headache-related disability, and reduced quality-oflife than do migraineurs with neither comorbid condition. 12 An emerging body of literature suggests that psychiatric comorbidity also portends a poorer prognosis for response to headache treatment. 2,13 Despite this evidence, there is a relative paucity of research investigating the effects of treating psychiatric disorders on headache or the converse, on the impact of treating headache on psychiatric disorders.…”
Section: Why Screen For Psychiatric Disorders?mentioning
confidence: 99%
“…In another population based study in France, more than half of the migraine sufferer stated adverse impact of migraine on their daily living (12). There are plenty of studies on the effect of therapeutic or prophylactic management of the migraine on HRQOL.…”
Section: Introductionmentioning
confidence: 99%